2(3+4x)=46

Simple and best practice solution for 2(3+4x)=46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3+4x)=46 equation:


Simplifying
2(3 + 4x) = 46
(3 * 2 + 4x * 2) = 46
(6 + 8x) = 46

Solving
6 + 8x = 46

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 8x = 46 + -6

Combine like terms: 6 + -6 = 0
0 + 8x = 46 + -6
8x = 46 + -6

Combine like terms: 46 + -6 = 40
8x = 40

Divide each side by '8'.
x = 5

Simplifying
x = 5

See similar equations:

| 9x+25=81 | | 3x-5+6x-2=5x+4x+7 | | 4x-5-3x=0 | | 9+25=81 | | .8w-.7w+.4w=3 | | x^2-10x+28=x^2+x+8 | | 2h+4=23-h | | Bx+Dy=L | | 4y+2x=-22 | | -(6x+2)-(8x-3)=8-(5x+1) | | x^2-10x+28=x^2+x+28 | | -4x-4=4x+4 | | 3x+36-37(4x)=707 | | c^2+5c+25= | | 0.6875=11*0.0625 | | 6.2h+1.4h=4.8h+5 | | 8.25x+6.25y=588 | | -2(x-18)+4(x+3)=x-6 | | 0.6875=.11*0.0625 | | 9(4x-3)=-3(12x+4) | | 2-6x=-40 | | 6x-5=4-2x | | x+y=6000 | | .4x-.36x=2 | | 5y-5(6-2y)=0 | | -18y+17=-29 | | 12r+3r^2=r^2-4r | | .5b(2)=20 | | 7-(3x-1)=7-4x | | 5.4t+14.6-10.1t=12.8-0.6 | | 8*b=819 | | -2(1+r)=16 |

Equations solver categories